Maqāṣid al-Sharī‘ah Review of Government Policy on the Free Nutritional Meal Program (MBG): A Comparative Study in Uṣūl al-Fiqh - Neng Yani Nurhayani; RR. Rita Erawati; Erika Rishan Adillah; Ending Solehudin; Syahrul Anwar (UIN Sunan Gunung Djati Bandung, 2026)
This study examines the alignment of Indonesia’s Free Nutritious Meals (MBG) policy with the principles of Maqāṣid al-Sharī‘ah through a normative juridical and comparative uṣūl al-fiqh approach. Focusing on hifẓ al-nafs and hifẓ al-māl, it finds that although MBG supports the preservation of life, its technocratic implementation has yet to embody maqāṣid values comprehensively, particularly regarding distributive justice, prioritization of benefits across ḍarūriyyāt, ḥājiyyāt, and taḥsīniyyāt, and long-term social welfare. The study highlights gaps such as unequal distribution, budget constraints, and weak monitoring, and argues for more adaptive, welfare-oriented policy formulation that integrates both classical emphases on basic needs and contemporary concerns for structural justice and sustainable welfare.